Provider and community stakeholder perspectives of expanding Medicaid coverage of abortion in Illinois - Carmela Zuniga; Aalap Bommaraju; Lee Hasselbacher; Debra Stulberg; Terri-Ann Thompson (BMC, 2022)
Abstract Background Many people seeking abortion encounter financial difficulties that delay or prevent them from accessing care. Although some patients qualify for Medicaid (a public program that can help cover health care costs), laws in some states restrict the use of Medicaid for abortion care. In 2017, Illinois passed House Bill 40 (HB-40), which allowed patients with Medicaid to receive coverage for their abortion. This study aimed to understand how HB-40 affected abortion affordability from the perspectives of individuals that work directly or indirectly with abortion patients or facilities providing abortion care. Methods We conducted interviews with clinicians and administrators from facilities that provided abortion services; staff from organizations that provided resources to abortion providers or patients; and individuals at organizations involved in the passage and/or implementation of HB-40. Interviews were audio-recorded and transcribed. We created codes based on the interview guides, coded each transcript using the web application Dedoose, and summarized findings by code. Results Interviews were conducted with 38 participants. Participants reflected that HB-40 seemed to remove a significant financial barrier for Medicaid recipients and improve the experience for patients seeking abortion care. Participants also described how the law led to a shift in resource allocation, allowing financial support to be directed towards uninsured patients. Some participants thought HB-40 might contribute to a reduction in abortion stigma. Despite the perceived positive impacts of the law, participants noted a lack of public knowledge about HB-40, as well as confusing or cumbersome insurance-related processes, could diminish the law's impact. Participants also highlighted persisting barriers to abortion utilization for minors, recent and undocumented immigrants, and people residing in rural areas, even after the passage of HB-40. Conclusions HB-40 was perceived to improve the affordability of abortion. However, participants identified additional obstacles to abortion care in Illinois that weakened the impact of HB-40 for patients and required further action, Findings suggest that policymakers must also consider how insurance coverage can be disrupted by other legal barriers for historically excluded populations and ensure clear information on Medicaid enrollment and abortion coverage is widely disseminated.